Exploring the intricacies in the conduction mechanism of the perovskite series Ba2HoSb1−xRuxO6: A conductivity scaling approach. (March 2020) - Halder, Saswata; Kumar, Ram Awdhesh; Dutta, Alo; Sinha, T.P.
Abstract: A composition-dependent investigation of the electrical conductivity and electric modulus formalisms was performed for complex perovskites of the form Ba2 HoSb1- x Ru x O6 ( x = 0.25, 0.50, 0.75, 1.0). The combination of X-ray diffraction and Rietveld refinement methods confirmed the structure of all the synthesized samples to be cubic. The lattice parameters and cell volumes of the synthesized materials satisfy the linear Vegard law, confirming the formation of complete solid solutions. The strength of bonding in the materials was analysed through the bond valence sum approach as a function of changing composition. The electrical conductivity trends were investigated as a function of Ru substitution. A scaling formalism satisfying the time–temperature superposition principle as functions of temperature and composition was sought. The activation energies extracted from the dc conductivity and hopping frequency show positive correlation. The scaled conductivity and modulus curves do not form a master curve in the grain and grain-boundary regions because of the dissimilar activation kinetics in the microstructures. Thus, the scaling remains inconsistent in these microstructural domains. However, a perfect scaling of the conductivity is found as a function of composition. Thus, the conduction mechanism follows a mobility scaling rather than a temperature scaling. A perfect scaling of the electric modulus as a function of composition is not found, showing the pronounced compositional dependence of the relaxation mechanism. Thus, the scaling behaviour has threefold implications: (i) there is no single universal scaling parameter for the conductivity spectra in the different electroactive microstructural domains, (ii) there is a unique scaling function over composition which can account for both temperature-independent and composition-independent conduction processes and (iii) it points towards a composition-independent conduction mechanism in contrast to a composition-dependent relaxation mechanism. Highlights: Complex perovskite oxides have been synthesized by a solid-state reaction technique. The structural evolution of the materials is investigated as a function of composition. The electrical conductivity is dependent on the Ru 4d–O 2p bandwidth. The scaling behaviour with temperature is not universal in all microstructural domains. Conduction and relaxation processes show contrasting dependence on composition.